Targeting IT Opportunities at Target - Alghalith, Nabil (Journal of Strategic Innovation and Sustainability, 2018)
The goal of this paper is to develop a case study that involves a thorough analysis of the strategic and operational impact of the implementation of IT at Target. The paper examines the following aspects of Target: (1) History and background, (2) Organization structure, (3) Business model, (4) Business and competitive environment, (5) Information technology architecture, (6) E-commerce systems, (7) IT deployment and assessment, and (8) Conclusion and lessons learned. Value chain, SWOT, strategic matrix, and the competitive forces models are used to assess the impacts of IT implementation on the corporate competitiveness, organization structure, decision making, systems integration, streamlining and automation of operations, and control.